Growth and grazing of the chlorarachniophyte Bigelowiella natans (Chlorarachniophyceae) on the marine cyanobacterium Synechococcus. Issue 4 (4th July 2021) - Yoo, Yeong Du; Palenik, Brian
ABSTRACT: Chlorarachniophytes are cosmopolitan, typically unicellular marine phototrophic protists with green plastids of secondary endosymbiotic origin. However, there are few studies of their eco-physiology. Bigelowiella natans feeds mixotrophically on diverse strains of Synechococcus . We investigated feeding by B. natans (Chlorarachniophyceae) on diverse strains of the marine cyanobacterium Synechococcus and quantified the ingestion and clearance rates of B. natans on Synechococcus strains CC9311 and CC9605 as a function of prey concentration, as well as the growth rates of B. natans feeding on these Synechococcus strains. The maximum ingestion rates of B. natans on Synechococcus strains CC9311 and CC9605 were 2.77 and 2.18 cells predator –1 h –1, respectively. The maximum clearance rates of B. natans on Synechococcus CC9311 and CC9605 were 197.2 and 331.5 nl predator –1 h –1, respectively. The maximum mixotrophic growth rates of B. natans on Synechococcus CC9311 and CC9605 were 0.38 d –1 and 0.28 d –1, respectively, while its autotrophic growth rates were 0.174 ± 0.019 d –1 . The results of the present study suggest that B. natans is an effective protistan grazer of Synechococcus and that it obtains a significant ecological advantage from a mixotrophic strategy in marine planktonic food webs.